Isolation of epithelial cells, villi and crypts from small intestine of pigeons (Columba livia) - Mac Donal, Oscar (2008)
The isolation of viable enterocytes, villi and crypts from the small intestine of a feral bird (Columba livia) is important for performing physiological experiments in ecologically relevant processes of membrane transport. The effectiveness of mechanical disruption, enzymatic digestion and chelating agents were compared. The objectives were to isolate enterocytes, villi and crypts from the small intestine of young pigeons; to evaluate the viability of the isolated intestinal epithelial cells isolated; and to verify the integrity of enterocytes by biochemical features. Enzymatic and mechanical methods yielded both elongated columnar and spherical cells. With the chelating method villi and crypts were obtained. All methods produced a high yield of intestinal epithelial cells with about 50 % viability. Brush border enzymes (sucrase-isomaltase and alkaline phosphatase) activities were high and, as reported in chickens, they did not differ along the intestinal villus-crypt axis. Although the three methods have good viabilities, the enzymatic technique gives the best yield in cell number, while the chelating method provides the highest populations of morphologically distinctive villi and crypts.